Management of collar rot of pea by the integration of biological and chemical methods - S.C. DUBEY*, DEEPAK KUMAR and (Indian Phytopathology, 2002)
Isolates of Trichoderma viride, T. harzianum and Gliocladium virens were screened against Fusarium solani f. sp. pisi causing collar rot of pea through dual culture and production of volatile and non-volatile antibiotic substances in vitro. The Ranchi isolate of T. harzianum and G. virens showed superiority over other isolates in respect of inhibition of mycelial growth of the pathogen. T. harzianum showed maximum growth around the treated seed followed by G. virens, thiram + G. virens, carboxin + G. virens, captan + G. virens and captan + T. harzianum which were statistically at par. The seeds treated with captan (1 glkg) + T. harzianum (106 spores/mVl0g seed) gave good germination, least disease incidence along with highest green pod yield, which was statistically similar with seed treated with T. harzianum alone, thiram + T. harzianum, carboxin + G. virens and G. virens alone.